PENGARUH STRATEGI BELAJAR PQ4R TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V SEKOLAH DASAR - Sinta, Sinta; Halidjah, Siti; Kresnadi, Hery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aimed to analyze the effect of learning strategies preview, question, read, reflect, recite, review (PQ4R) on reading comprehension skills of class V students of Pontianak City 66 Elementary School. The method used is the experimental method, while the form of research used is quasi experimental design with nonequivalent control group design. The population and sample in this study were all fifth grade students of Pontianak City 66 Elementary School. The data collection tool used was a multiple choice test with 45 questions. Based on data analysis, the average post-test results of the experimental class were 81.31 while the average post-test results of the control class were 63.18. The results of the t test are obtained tcount of 7.682 and t table Î± = 5% (with dk = 33 + 32 - 2 = 63) of 1,999, which means tcount (7,682 )> t table (1,999), then the alternative hypothesis (Ha) is accepted. It can be concluded that there is influence learning strategies preview, question, read, reflect, recite, review (PQ4R) on comprehension reading skills in class V of Pontianak City 66 State Elementary School. From the results of the calculation of the effect size (ES) ES obtained is 1.4 (high criteria). This means that the learning strategies of preview, question, read, reflect, recite, review (PQ4R) have a good influence on reading comprehension skills of class V students of Pontianak City 66 Elementary School.Â Keywords: Â Preview, Question, Read, Reflect, Recite, Review (PQ4R), Reading Skills, Reading Comprehension